Production, Characterization and Surface Properties of Sr Doped Hydroxyapatite Coating on Magnesium Alloy by Hydrothermal Method - Gürgenç, Turan (My University, 2020)
In this study, the surface of AZ91D magnesium alloy was coated with undoped and at different ratios strontiumdoped hydroxyapatite. Coatings were carried out at 180 °C in 3 hours. The surface roughness of the coatedsamples was determined and the microstructure of the phases forming on the coated surfaces were examinedby scanning electron microscopy (SEM). The chemical composition of the phases formed on the coated surfaceswas determined by energy dispersed X-ray spectroscopy (EDS). The phases formed on the surfaces werecharacterized by X-Ray diffraction (XRD) and Fourier transform infrared spectrometry (FT-IR). The AZ91Dmagnesium alloy was coated successfully with undoped and strontium doped hydroxyapatite by hydrothermalmethod. The highest surface roughness value was measured as Ra = 8.255 µm in 15% strontium doped sample.It was determined that the (Ca + Sr) / P ratios of the coatings were higher than the stoichiometric ratio ofhydroxyapatite, 1.67. It was determined that the closest coating to the stoichiometric ratio was 10% Sr dopedcoating.
Keywords: Mühendislik; Biyotıp; Nanobilim ve Nanoteknoloji; Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Biyomalzemeler